Analysis of Written Mathematics Communication Skills in Solving Solo Taxonomy Assisted Problems - Sekaryanti, Ridina; Cholily, Yus Mochamad; Darmayanti, Rani; Rahma, Kamilia; Maryanto, Bhaskoro Prasetyo Adi (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
The purpose of this study was to determine students' written communicative competence in solving key problems of SPLDV in everyday life. This study uses descriptive qualitative research. These data are determined by testing. Subjects in this study consisted of her three undergraduates from UTS results. The three students were made up of representatives of high, middle and low ability students. In addition, students are given test questions supported by the SOLO taxonomy of SPLDV materials, which are analyzed according to indicators of mathematical communicative competence. The bottom line is that students with good math skills are able to give correct and correct answers, but have not yet reached the level of extended abstraction. A student with moderate writing ability can demonstrate the correct procedure, but still has problems using and processing the information, so the answers are wrong and only reach the polystructural level. Students with low mathematics ability do not solve problems, only part of the problem is presented, so they only reach the monostructural level and most of the answers are wrong.